Husband's Support for Adherence of Pregnant Women Consuming Iron Folic Acid - Hanie Kusuma Wardani (Universitas STRADA Indonesia, 2022)
Stunting is a global problem, including in Indonesia. UNICEF reports the incidence of stunting in Indonesia that in 2018, almost 3 in 10 children under five years of age were stunted or too short for their age, while 1 in 10 was underweight or too thin for their age. Various efforts to prevent stunting have been carried out by the Indonesian government, one of them is iron supplementation for pregnant women. The success of this program is largely determined by the adherence of pregnant women in consuming iron supplement that they receive. This study aims to determine the effect of husband's support on the adherence of pregnant women in consuming iron supplements. This research is a literature study by reviewing 15 journals related to the influence of husband's support on the adherence of pregnant women in consuming iron supplements. The type of data used is secondary data. The method of data collection is literature study. The method that will be used for the assessment is a literature study. The data obtained were compiled, analyzed, and concluded so as to obtain conclusions regarding the study of literature. Total of 15 articles were reviewed, all of which were written from 2015 – 2021. All articles concluded that there was a significant relationship between husband's support for pregnant women's adherence to iron supplements. Conclusion: Based on previous research, it can be concluded that husband's support increases the adherence of pregnant women in consuming iron supplements.